A Study Of The Misuse Of Drugs Among Secondary School Children In The State Of Kelantan. - Spencer, Dr. C. P.; Navaratnam, V.; Lee, Boon Aun

(untitled)
Adolescent drug abuse in Malaysia - a phenomenon of the late 1960 l s and the 1970's - has been the cause of considerable public concern and discussion but, until recently, much of the discussion was necessarily founded upon speculation, for there was little systematic collecting of information on the extent and nature of the problem.